Abstract 244: Effect of Actuation Frequency on Clot Integration with the Tigertriever Device: An In Vitro Study - Nakisa Dashti; Megha Gopal; Rowan J Serna; David Fiorella; Chander Sadasivan (Stroke: Vascular and Interventional Neurology)
Introduction Mechanical thrombectomy has been widely recognized as the preferred treatment for large vessel occlusion strokes. The Tigertriever stent‐retriever (Rapid Medical, Yokneam, Israel) is a novel operator‐adjustable device that can be actively expanded and contracted by the operator [1], which allows for several actuation‐related parameters to be optimized to potentially improve device efficacy. These parameters – such as amplitude and frequency of the actuation cycle, and rate of expansion and contraction – have not yet been evaluated in correlation with device success. We conducted a benchtop study to evaluate the effect of actuation frequency on clot integration within the stent. Methods A Tigertriever 17 device was deployed within a biological thrombus analog (2.5 cm length) placed in a straight silicone tube (2.4 mm diameter). The device was actuated between the maximally contracted and maximally expanded states with three different frequencies: Passive (one‐time opening, n=6), Slow (20 seconds/cycle, n=6), and Fast (5 seconds/cycle, n=7). A flat‐detector CT scan was acquired, the clot and stent wires were segmented, and the boundaries of the clot and stent wires were calculated on each axial slice (Figure 1A). The intersection between the stent and clot boundaries throughout the volume was defined as the volume of clot integrated within the stent. The clot integration factor (CIF, ratio of integrated clot volume to total clot volume) was then statistically compared between the three frequencies as an estimate of clot capture efficiency. Results The CIF was significantly higher (23% increase, p=0.01) with the Fast actuation as compared to the Passive and Slow actuations, with a post‐hoc test showing no difference (p>0.05) between the Passive and Slow actuation frequency (Figure 1B). Conclusion The unique malleability of the Tigertriever stent‐retriever (Rapid Medical) presents an opportunity to better understand actuation parameters that can maximize thrombus capture. Results indicate that faster actuation frequencies may result in improved clot integration with the Tigertriever device. These results are concordant with a previous clinical study [1] that found repetitive‐expansion‐contraction was more successful than single unsheathing (which corresponds to our Passive group). It is possible that the greater acceleration of the stent mesh wires in the Fast actuation frequency resulted in increased radial forces that improved clot integration. This effect must be further validated in an in vitro setting more representative of physiological conditions, as well as eventual clinical evaluation.